The need for congestion pricing in medellin: an economic perspective (2012)
This paper presents a brief description of vehicular congestion in Medellin, Colombia, and discusses the need to implement congestion pricing (CP) from an economic point of view. It describes the license plate-based traffic restriction (Pico y Placa) in the city, showing that the measure is palliative, and that the implementation of CP is necessary. A cost-benefit analysis is presented to assess the effects of implementing a hypothetical CP strategy based on data from previous studies. The first-best solution for CP is presented, and considered as the optimal policy for deciding on the congestion rate that would maximize social welfare. The main finding is that the net benefit of implementation costs is positive. Therefore, the implementation of a CP strategy is recommended to improve the efficiency of road infrastructure use in the city based on economic principles. Finally, a set of recommendations for improving the city's mobility in the future are presented.